2016
DOI: 10.17140/whoj-1-109
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Correlates, and the Marital Relationship in Women with Breast Cancer in Saudi Arabia

Abstract: ResearchPage 53 ABSTRACTThe relationship between the quality of the marital relationship and depressive symptoms in married women with breast cancer in Jeddah, Saudi Arabia, was examined. A consecutive series of 50 women with breast cancer were interviewed using a close-ended questionnaire. Over 20% of women had depressive symptoms indicating a probable depressive disorder using the Hospital Anxiety and Depression Scale. Although a weak relationship in the expected direction was found, quality of the marital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…In our results, the prevalence of depression was higher than other Saudi studies [21]. The high rates of depression in the current study could be explained by including many cancers, whereas the previous Saudi study included only breast cancer patients.…”
Section: Depression Onlycontrasting
confidence: 80%
“…In our results, the prevalence of depression was higher than other Saudi studies [21]. The high rates of depression in the current study could be explained by including many cancers, whereas the previous Saudi study included only breast cancer patients.…”
Section: Depression Onlycontrasting
confidence: 80%
“…Morbidity was also found to be a significant predictor of women’s ill-being in Riyadh. Evidence on the effect of morbidity on mental health and ratings of health in general has been well established [ 34 , 35 , 36 , 37 , 38 ]. Studies conducted among the general population reported that chronic conditions can have a negative impact on health perceptions [ 35 , 36 ] and quality of life [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the effect of morbidity on mental health and ratings of health in general has been well established [ 34 , 35 , 36 , 37 , 38 ]. Studies conducted among the general population reported that chronic conditions can have a negative impact on health perceptions [ 35 , 36 ] and quality of life [ 34 ]. Another study, among a community sample in Hong Kong, showed a higher prevalence of depressive symptoms among people with one or more chronic physical illnesses; depressive symptoms were more prevalent among females [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Kingdom of Saudi Arabia (KSA), breast cancer has been the most common cancer prevailed among women for past twelve years. 19 , 20 Breast cancer is considered as the most common cancer among the females of Saudi Arabia despite of its low incidence. The factors increasing the risk of developing breast cancer include; genetic background or family history (15%), hormonal imbalance, increased breast density, and history of benign proliferative breast disease.…”
Section: Discussionmentioning
confidence: 99%
“…The factors increasing the risk of developing breast cancer include; genetic background or family history (15%), hormonal imbalance, increased breast density, and history of benign proliferative breast disease. 20 Late stage occurrence in young women is a serious issue, particularly in countries like Saudi Arabia, where the development of breast cancer is rising with the time and evolving at younger ages. 21 The cancer cells are predisposed due to constitutional inactivating mutations in genes encoding the protein that are important for DNA repairing.…”
Section: Discussionmentioning
confidence: 99%